Serum amyloid A1 mediates myotube atrophy via Toll‐like receptors - Alexander Hahn; Melanie Kny; Cristina Pablo‐Tortola; Mihail Todiras; Michael Willenbrock; Sibylle Schmidt; Katrin Schmoeckel; Ilka Jorde; Marcel Nowak; Ernst Jarosch; Thomas Sommer; Barbara M. Bröker; et al. (Wiley, 2020)
Abstract Background Critically ill patients frequently develop muscle atrophy and weakness in the intensive‐care‐unit setting [intensive care unit‐acquired weakness (ICUAW)]. Sepsis, systemic inflammation, and acute‐phase response are major risk factors. We reported earlier that the acute‐phase protein serum amyloid A1 (SAA1) is increased and accumulates in muscle of ICUAW patients, but its relevance was unknown. Our objectives were to identify SAA1 receptors and their downstream signalling pathways in myocytes and skeletal muscle and to investigate the role of SAA1 in inflammation‐induced muscle atrophy. Methods We performed cell‐based in vitro and animal in vivo experiments. The atrophic effect of SAA1 on differentiated C2C12 myotubes was investigated by analysing gene expression, protein content, and the atrophy phenotype. We used the cecal ligation and puncture model to induce polymicrobial sepsis in wild type mice, which were treated with the IкB kinase inhibitor Bristol‐Myers Squibb (BMS)‐345541 or vehicle. Morphological and molecular analyses were used to investigate the phenotype of inflammation‐induced muscle atrophy and the effects of BMS‐345541 treatment. Results The SAA1 receptors Tlr2, Tlr4, Cd36, P2rx7, Vimp, and Scarb1 were all expressed in myocytes and skeletal muscle. Treatment of differentiated C2C12 myotubes with recombinant SAA1 caused myotube atrophy and increased interleukin 6 (Il6) gene expression. These effects were mediated by Toll‐like receptors (TLR) 2 and 4. SAA1 increased the phosphorylation and activity of the transcription factor nuclear factor 'kappa‐light‐chain‐enhancer' of activated B‐cells (NF‐κB) p65 via TLR2 and TLR4 leading to an increased binding of NF‐κB to NF‐κB response elements in the promoter region of its target genes resulting in an increased expression of NF‐κB target genes. In polymicrobial sepsis, skeletal muscle mass, tissue morphology, gene expression, and protein content were associated with the atrophy response. Inhibition of NF‐κB signalling by BMS‐345541 increased survival (28.6% vs. 91.7%, P < 0.01). BMS‐345541 diminished inflammation‐induced atrophy as shown by a reduced weight loss of the gastrocnemius/plantaris (vehicle: −21.2% and BMS‐345541: −10.4%; P < 0.05), tibialis anterior (vehicle: −22.7% and BMS‐345541: −17.1%; P < 0.05) and soleus (vehicle: −21.1% and BMS‐345541: −11.3%; P < 0.05) in septic mice. Analysis of the fiber type specific myocyte cross‐sectional area showed that BMS‐345541 reduced inflammation‐induced atrophy of slow/type I and fast/type II myofibers compared with vehicle‐treated septic mice. BMS‐345541 reversed the inflammation‐induced atrophy program as indicated by a reduced expression of the atrogenes Trim63/MuRF1, Fbxo32/Atrogin1, and Fbxo30/MuSA1. Conclusions SAA1 activates the TLR2/TLR4//NF‐κB p65 signalling pathway to cause myocyte atrophy. Systemic inhibition of the NF‐κB pathway reduced muscle atrophy and increased survival of septic mice. The SAA1/TLR2/TLR4//NF‐κB p65 atrophy pathway could have utility in combatting ICUAW.